Employee inspecting solvent recovery system at Hercules Hopewell plant - Hercules Incorporated (1940)
General view of an unidentified employee inspecting the control board for a Solvent Recovery system at the Hercules Powder Company plant in Hopewell, Virginia. Per notations accompanying the photograph, the system was used to separate ethyl chloride, ether, and alcohol, likely during the production of so-called "chemical cotton," a type of purified cellulose obtained from raw cotton linters. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Hercules Incorporated; Corporations; Cellulose; Machinery